Expressions of miR-132, miR-134, and miR-485 in rat primary motor cortex during transhemispheric functional reorganization after contralateral seventh cervical spinal nerve root transfer following brachial plexus avulsion injuries. Issue 1 (6th January 2016) - Wang, Xin-Hong; Li, Li-Jun; Sun, Gui-Xin; Wu, Zuo-Pei; Li, Ji-Feng; Gu, Yu-Dong
Abstract : The transfer of a contralateral healthy seventh cervical spinal nerve root (cC7) to the recipient nerve in the injured side is considered a promising procedure for restoration of the physiological functions of an injured hand after brachial plexus root avulsion injury (BPAI). Growing evidence shows that transhemispheric cortical reorganization plays an important role in the functional recovery of the injured arm after cC7 nerve transfer surgery. However, the molecular mechanism underlying the transhemispheric cortical reorganization after cC7 transfer remains elusive. In the present study, we investigated the expression of miR-132, miR-134, and miR-485 in the rat primary motor cortex after cC7 transfer following BPAI by quantitative PCR. The results demonstrated the dynamic alteration in the expression of miR-132, miR-134, and miR-485 in the primary motor cortex of rats after cC7 transfer following BPAI. It indicates that microRNAs are involved in the dynamic transhemispheric functional reorganization after cC7 root transfer following BPAI. Together, this study is the first to provide evidence for the involvement of microRNAs during dynamic transhemispheric functional reorganization after cC7 transfer following BPAI. The results are useful for understanding the mechanism underlying transhemispheric functional reorganization after contralateral seventh cervical spinal nerve root transfer following BPAI.